Clinical and Radiological Outcomes of Two-Stage Revision Knee Arthroplasty in Infected Primary Knee Arthroplasty - Ahmet Şenel; Yusuf Öztürkmen; Ziya Demirci; Atakan Telatar; Murat Eren; Erhan Şükür; Yunus Emre Akman (İstanbul Medical Journal, 2023)

(untitled)
Introduction:Two-stage revision arthroplasty is the gold standard treatment for infected knee arthroplasty. The primary objectives of this treatment approach are to eradicate the infection and restore a pain-free and well-functional joint. In this retrospective study of case series from a single center, we aimed to evaluate the clinical and radiological results of patients who underwent two-stage revision knee replacement with the diagnosis of infected knee prosthesis and share the results.Methods:The data of patients between 2011 and 2016 were analyzed in this retrospective study. Twenty-four patients who were followed up for at least six months were included in the study. Infection markers, Knee Society Score (KSS), pain scores, range of motion (ROM), and flexion contractures were recorded before and after treatment. Radiologically, changes in the patellar tendon length, the Insall-Salvati (IS) ratio, and the joint line (JL) were evaluated.Results:Sixteen female and eight male patients with a mean age of 68.0±8.6 years were studied. The patients were followed up for 31.0±18.9 months on average. The mean clinical KSS of the patients before and after treatment was 44.7 and 76.3, respectively, while the functional KSSs were 31.7 and 63.5, respectively. The patients had a mean ROM of 60.5° and 84.8°, pain score of 8 and 2.25, and knee flexion contracture of 1.38° and 0.21° before and after the treatment. Pre- and post-treatment IS and JL values did not have a statistically significant effect on the clinical and functional outcomes.Conclusion:The early- tomid-term results of patients who underwent two-stage knee revision arthroplasty were satisfactory in terms of clinical and functional results. Postoperative JL position and IS ratio had no significant effect on functional outcomes. The use of dynamic spacers and the short time between two stages had a positive effect on the results.